Usia Dan Posisi Kerja Pengrajin Payet Berpengaruh Terhadap Keluhan Low Back Pain - Izmaul Husna; Arifin Arifin; Gunung Setiadi (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2021)
Low Back Pain (LBP) is one of the musculoskeletal disorders, psychological disorders and the result of wrong mobilization. LBP is one of the most common health problems in the industrial community, one of which is Payet Craftsmen. The purpose of this study was to determine the relationship between age and work position with LBP complaints on Halidah Sequin Craftsmen in Cempaka Sub-District. Analytical research design with approach cross sectional. The sample in this study were workers who met the inclusion criteria amounting to 25 people. Data analysis used chi-square test. Test results of research was the age variable is sig value 0.122 (> 0.05). meaning that there is no relationship between age variable with LBP complaints on Halidah Sequin Craftsmen in Cempaka Sub-District. While test results of research was the variable work position is a sig value of 0.022 (< 0.05). meaning that there is a relationship between work position variable and LBP complaints on Halidah Sequin Craftsmen in Cempaka Sub-District, with an Odds Ratio of 8,000 means that respondents who have high risk work positions are 8 more risk to complain of LBP compared to respondents who have moderate risk work positions.